Misfit landforms imposed by ill-conditioned inverse parametric problems - Łoś, Marcin Mateusz; Smołka, Maciej; Schaefer, Robert; Sawicki, Jakub (Wydawnictwa AGH, 2018)
In this paper, we put forward a new topological taxonomy that allows us to distinguish and separate multiple solutions to ill-conditioned parametric inverse problems appearing in engineering, geophysics, medicine, etc. This taxonomy distinguishes the areas of insensitivity to parameters called the landforms of the misfit landscape, be it around minima (lowlands), maxima (uplands), or stationary points (shelves). We have proven their important separability and completeness conditions. In particular, lowlands, uplands, and shelves are pairwise disjoint, and there are no other subsets of the positive measure in the admissible domain on which the misfit function takes a constant value. The topological taxonomy is related to the second, »local« one, which characterizes the types of ill-conditioning of the particular solutions. We hope that the proposed results will be helpful for a better and more precise formulation of ill-conditioned inverse problems and for selecting and profiling complex optimization strategies used in solving these problems.
Computer Science
Bibliogr. s. 176-177.
Keywords: taxonomy of ill-conditioned problems; ill-posed global optimization problems; fitness landscapes